PELAKSANAAN KONTRAK HARGA SATUAN PADA PAKET PERKERJAAN KONSTRUKSI PEMBANGUNAN PENGAMANAN PANTAI PULAU TERLUAR PROVINSI RIAU ANTARA PT.ALEX PUTRA SAKTI DENGAN PEJABAT PEMBUAT KOMITMEN SUNGAI DAN PANTAI DI DESA CENTAI KECAMATAN PULAU MERBAU KABUPATEN KEPULAUANMERANTI - Ananda Fernando Putra; Mardalena Hanifah; Setia Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Currently, in the implementation of goods and services procurement work, including constructionservices, the total costs of which are borne by the State Budget (APBN) and the RegionalExpenditure Budget (APBD), must comply with statutory provisions. To carry out development, thegovernment needs other parties, after that the government takes the option of conducting a selectionin the form of an auction. After obtaining the winning bidder, the Government will draw up aConstruction Work Contract. In the implementation of the Construction Work Contract between theCommitment Making Officer (PPK) and PT Alex Putra Sakti in the construction of Coastal Securityfor the Outermost Islands of Riau Province in Centai Village, Merbau Island District, MerantiRegency, the implementation procedure must comply with applicable regulations. Therefore, thepurpose of this study was to find out the implementation of unit price contracts in the constructionwork package for the construction of coastal safeguards in the outermost islands of Riau Provincebetween PPK PT Alex Putra Sakti and officials making river and beach commitments in CentaiVillage, Merbau Island District, Meranti Regency.The type of research in this paper is sociological legal research, namely research conducted byidentifying and how effective it is in society or reviewing the state of the problem associated withthe applicable legal aspects and judging from its descriptive nature, namely describing the process.From the results of the research, there are two main things: First, that the Procedure forImplementation of the Construction Contract for the construction of beach security in the MerantiVillage of Centai Regency is running in accordance with the agreed work contract and inaccordance with the Law of the Republic of Indonesia Number 18 of 1999 concerning servicesconstruction. Second, in the process of carrying out the completion of the work there were obstaclesexperienced by the contractor, namely the implementation exceeded the time limit for 14 days sothat the ppk was required to make compensation for a delay of 1/1000 of the contract value that hadbeen agreed upon, this delay was due to high tide or volume from rising sea water o that theconstruction work of protecting the coast experienced delays in its implementation covid19.Keywords: Implementation of development construction work contract